Surface studies on benzophenone doped PDMS microstructures fabricated using KrF excimer laser direct write lithography - Kant, Madhushree Bute; Shinde, Shashikant D.; Bodas, Dhananjay S.; Patil, K. R.; Sathe, V. G.; Adhi, K. P.; Gosavi, S. W. (Applied Surface Science, 2014)
his paper discusses microfabrication process for benzophenone doped polydimethylsiloxane (PDMS) using laser lithography. KrF excimer laser of 248 nm with 20 ns pulse width at repetition rate of 1 Hz was used for microfabrication of undoped and benzophenone doped PDMS. The doped-PDMS shows sensitivity below 365 nm, permitting processing under ambient light. The analysis of etch depth revealed that doped PDMS shows self developable sensitivity at lower fluence of similar to 250 mJ/cm(2). The unexposed and exposed surface was studied using Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and Scanning electron microscopy (SEM). Spectrocopic analysis indicated increase in C-O, C=O, Si-O-3 and Si-O-4 bonding at the expense of Si-C and Si-O-2 bonds of PDMS. In case of laser exposed doped-PDMS, removal of benzophenone from probe depth of spectroscopy was observed. Whereas the surface morphology of exposed and unexposed doped-PDMS was observed to be same, indicating clean development of PDMS micropattems. The present study indicates that addition of 3.0 wt.% benzophenone in PDMS enhance self development sensitivity of PDMS. The self developable results on doped-PDMS are quite encouraging for its potential use in point of care Lab-On-Chip applications, for fabricating micropattems using direct write laser lithography technology.
Keywords: Direct write laser lithography; Microfabrication; micropatterning; Poly(dimethylsiloxane) (PDMS)